Opportunities for all the Team: Entrepreneurship and the 1966 and 1994 Soccer World Cups. Issue 7 (24th May 2018) - Tennent, Kevin D.; Gillett, Alex G.
Abstract: Little research has been published as to the ways in which the commercial aspects of the Fédération Internationale de Football Association's (FIFA) World Cups are organized. Extant literature has instead tended to focus upon infrastructure issues, economic geography, and cultural aspects. Drawing upon 'swarm theory' and historian Wray Vamplew's typologies of entrepreneurial activity in sport, we compare and contrast the commercial aspects of two World Cups; first, the 1966 tournament held in England, the first time that a serious attempt had been made to produce and licence a mascot character ('World Cup Willie') to exploit merchandizing opportunities. This approach became an important part of World Cups thereafter; Second, the 1994 tournament in the USA, the most commercially successful World Cup ever, realizing record profits and catalyzing the re-launch of elite professional soccer in the USA. These cases enrich understanding of the networks and entrepreneurial activity of the World Cup, one of the most significant sporting and cultural mega-event projects in the world.